Dynamic-susceptibility contrast agent MRI measures of relative cerebral blood volume predict response to bevacizumab in recurrent high-grade glioma. Issue 6 (15th January 2014) - Schmainda, Kathleen M.; Prah, Melissa; Connelly, Jennifer; Rand, Scott D.; Hoffman, Raymond G.; Mueller, Wade; Malkin, Mark G.
Abstract: Background: The anti-VEGF antibody, bevacizumab, is standard treatment for patients with recurrent glioblastoma. In this setting, traditional anatomic MRI methods such as post-contrast T1-weighted and T2-weighted imaging are proving unreliable for monitoring response. Here we evaluate the prognostic significance of pre- and posttreatment relative cerebral blood volume (rCBV) derived from dynamic susceptibility contrast MRI to predict response to bevacizumab. Methods: Thirty-six participants with recurrent high-grade gliomas who underwent rCBV imaging 60 days before and 20–60 days after starting bevacizumab treatment were enrolled. Tumor regions of interest (ROIs) were determined from deltaT1 maps computed from the difference between standardized post and precontrast T1-weighted images. Both pre- and posttreatment rCBV maps were corrected for leakage and standardized (stdRCBV) to a consistent intensity scale. The Kaplan–Meier method was used to determine if either the pre- or post-bevacizumab stdRCBV within the tumor ROI was predictive of overall survival (OS) or progression free survival (PFS). Results: The OS was significantly longer if either the pre- (380d vs 175d; P =.0024) or posttreatment stdRCBV (340d vs 186d; P = .0065) was <4400. The posttreatment stdRCBV was also predictive of PFS (167d vs 78d; P = .0006). When the stdRCBV values were both above versus both below threshold, the OS was significantly worse (100.5d vs 395d; P < .0001). With a 32.5% decrease in stdRCBV, the risk of death was reduced by about 68% but increased by 140% with a 29% increase in stdRCBV. Conclusions: Standardized rCBV is predictive of OS and PFS in patients with recurrent high-grade brain tumor treated with bevacizumab.